Prognostic significance of histologic phenotype in periampullary adenocarcinomas - Kim, Hee-Sung; Heo, Chang-Min; Choi, Yoo-Shin; Suh, Suk-Won; Lee, Seung Eun (Frontiers in Oncology, 2024)
Background Periampullary adenocarcinomas typically exhibit either intestinal or pancreatobiliary (PB) differentiation, and the type of differentiation may be prognostically more important than the anatomic site of origin. This study aimed to evaluate prognostic significance of histological type of periampullary carcinomas. Methods Microscopic slides from 110 consecutive pancreatoduodenectomies performed between 2010 and 2020 were reviewed and classified as intestinal or PB type. Clinicopathological factors were compared between PB-(n=93) and intestinal-type (n=17) differentiation. Results The intestinal type included significantly more patients with well-differentiated histology (35.3% vs. 11.8%, p=0.001) and fewer patients with perineural invasion (41.2% vs. 76.4%, p=0.029), advanced T stage (> T3; 41.2% vs.74.2%, p=0.007), and systemic recurrence (71.4% vs. 92.9%, p=0.005) than PB type. The 5-year-overall survival rate of intestinal-type was significantly higher than that of PB-type (58.8% vs. 20.4%, p=0.003). When pancreatic cancer was separately analyzed, the intestinal type showed the best 5-year-overall survival rate, with no significant difference between the PB types excluding PDAC and PDAC (39.4% vs. 19.2%, p=0.148). In multivariate analysis, curative resection (hazard ratio, 0.417; 95% CI, 0.219-0.792, p=0.008) was the only significant prognostic factor. Conclusion Although intestinal histologic phenotype was not an independent prognostic factor on multivariate analysis, it showed pathologic features associated with better survival, while the PB type showed more aggressive tumor biology and consequently worse survival. Further studies are needed to demonstrate the prognostic significance of histologic phenotype.